2021
DOI: 10.51380/gujr-37-02-06
|View full text |Cite
|
Sign up to set email alerts
|

Nexuses of Ethical Leadership, Job Satisfaction and Job Performance in Academia of Khyber Pakhtunkhwa Pakistan

Abstract: Nowadays universities are going through the transition due which new performance standards have been created. In such situation, performance of employees can be enhanced through effective ethical leadership. The current study has examined the dynamic links between job satisfaction, job performance and ethical leadership in the academia of Pakistan. Using a cross sectional design, quantitative data were collected from 150 academic staff working in three universities. Data were analyzed both by descriptive and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 0 publications
6
30
0
1
Order By: Relevance
“…Thus, the hypothesis that RT significantly affects JS is accepted. This result is consistent with the study by 7,20,21,[26][27][28] . This confirms the hypothesis that RT has a positive influence on employees' JS.…”
Section: Results Of Model Testsupporting
confidence: 94%
See 4 more Smart Citations
“…Thus, the hypothesis that RT significantly affects JS is accepted. This result is consistent with the study by 7,20,21,[26][27][28] . This confirms the hypothesis that RT has a positive influence on employees' JS.…”
Section: Results Of Model Testsupporting
confidence: 94%
“…The result indicated that the relationship between BP and JS is significant at a coefficient of β = 0.236 (p= 0.001 < 0.01) and hypothesis H 3 was accepted. This result is also consistent with the study of 7,20,21,[26][27][28] . This confirms the hypothesis that BP has a positive influence on employees' JS.…”
Section: Results Of Model Testsupporting
confidence: 93%
See 3 more Smart Citations